Factors affecting postoperative nasal morphology after Le Fort I osteotomy on multiple regression analysis - Nobuyoshi Tomomatsu; Taishi Nakamura; Shin Matsumoto; Namiaki Takahara; Koichi Nakakuki; Yoshiyuki Sasaki; Tetsuya Yoda (Scientific Reports)
Abstract Changes in external nasal morphology after Le Fort I osteotomy can lead to reduced patient satisfaction and diminished quality of life postoperatively. Despite various modifications such as alar cinch suture and subspinal osteotomy to overcome such changes, the external nasal morphology may vary unexpectedly on an individual basis. This report investigated the factors influencing the changes in external nasal morphology, by considering the patient’s preoperative external nasal morphology as well as the surgical technique, and the direction of repositioning of maxilla. Multiple regression analysis identified the patient’s preoperative nasal width as a factor that increased the alar base width of the nose, in addition to incision (oral vestibular incision) and the amount of anterior and superior movements at point A of the maxilla. The factors that caused the nasal tip to turn upward were the amount of anterior and superior movements at point A and the absence of subspinal osteotomy. The direction of surgical maxillary movement was influenced not only by anterior movement, but also by superior movement and surgical technique. The patient’s preoperative nasal morphology should also be considered during the preoperative planning for orthognathic surgery to ensure optimal esthetic and functional outcomes.